Assessment of the Knowledge Regarding Diabetes Mellitus in Medical Students of Nepal - Joshi, Bishal; Pokharel, Buddhi Raj; Kar, Sanjit Kumar; Mahotra, Narayan Bahadur; Shrestha, Laxmi; Yadav, Shankar; Shrivastava, Amit Kumar (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Diabetes mellitus (DM) is a metabolic disorder with a very high prevalence. Adequate knowledge about diabetes mellitus is essential for medical students as they are future frontline warriors for its management. In the present study, we have attempted to assess the knowledge of medical students related to various aspects of DM. MATERIAL AND METHODS In this cross-sectional study, 445 medical students studying in the Universal College of Medical Sciences (UCMS), Bhairahawa, Nepal were included. A total of 20 self-designed questionnaires regarding DM were used as a study tool. Each question was allocated a score of one making 20 the highest possible score. The students who scored 13 (65%) or more were regarded as having good knowledge, and those scoring below 13 were considered as having poor knowledge related to DM. Statistical package for social sciences (SPSS) version 16 was used for data analysis. RESULTS Preclinical students were 309 (69.4%) and 136 (30.6%) clinical students. The mean knowledge score of the total participants were 13.54 ±3.68. The clinical students (16.23 ±2.26) were found to have better knowledge about DM than the preclinical students (12.36 ±3.56). Year wise evaluation showed that, on average, all except first-year students had good knowledge regarding DM, with the final year students having highest mean score (18.80 ±2.29). No significant difference in the knowledge was found between MBBS and BDS students. CONCLUSION The majority of the medical students had good basic knowledge regarding DM. Clinical students had significantly higher knowledge in comparison to preclinical students.